159k views
2 votes
Simplify the following expression

(2x3-x to the second power)(3x to the third power - 2x to the second power)

User Mottor
by
6.5k points

2 Answers

4 votes
remember

(x^m)(x^n)=x^(m+n)
and FOIL, a way to remember to distribute
First
Outer
Inner
Last
that is an order to multiply the terms

so


(2x^3-x^2)(3x^3-2x^2)
FOIL
First: 2x³ times 3x³=2 times x³ times 3 times x³=6x⁶
Outer: 2x³ times -2x²=-4x⁵
Inner: -x² times 3x³=-3x⁵
Last: -x² times -2x²=2x⁴

add them together
6x⁶-4x⁵-3x⁵+2x⁴=
6x⁶-7x⁵+2x⁴
User Nir Tzezana
by
6.8k points
2 votes
x^4(2x-1)(3x-2)
hope this helps :)

User Alexpanter
by
5.9k points